A Cross-Sectional Study on the Occurrence of the Intestinal Protist, Dientamoeba fragilis, in the Gut-Healthy Volunteers and Their Animals - Jirků, Milan; Kašparová, Andrea; Lhotská, Zuzana; Oborník, Miroslav; Brožová, Kristýna; Petrželková, Klára J; Samaš, Peter; Kadlecová, Oldřiška; Stensvold, Christen Rune; Jirků, Kateřina (International journal of molecular sciences, 2022)
Dientamoeba fragilis is a cosmopolitan intestinal protist colonizing the human gut with varying prevalence depending on the cohort studied and the diagnostic methods used. Its role in human health remains unclear mainly due to the very sporadic number of cross-sectional studies in gut-healthy populations. The main objective of this study was to expand knowledge of the epidemiology of D. fragilis in gut-healthy humans and their animals. A total of 296 stool samples from humans and 135 samples from 18 animal species were analyzed. Using qPCR, a prevalence of 24% was found in humans in contrast to conventional PCR (7%). In humans, several factors were found to influence the prevalence of D. fragilis. A more frequent occurrence of D. fragilis was associated with living in a village, traveling outside Europe and contact with farm animals. In addition, co-infection with Blastocystis spp. was observed in nearly half of the colonized humans. In animals, D. fragilis was detected in 13% of samples from eight species using qPCR. Our molecular phylogenies demonstrate a more frequent occurrence of Genotype 1 in gut-healthy humans and also revealed a likely a new protist species/lineage in rabbits related to D. fragilis and other related organisms.
Keywords: Feces; Cross-Sectional Studies; Prevalence; dientamébóza; Dientamoebiasis; animals; genotypes; survey; occurrence; human volunteers; prevalence; průřezové studie; Dientamoeba; Czech Republic; gut protist; zvířata; feces; Humans; králíci; sensitivity; Rabbits; demography; Dientamoeba fragilis; lidé; Animals